Intraoral Impalement Injury with Electric Toothbrush Head to the Infratemporal Fossa: A Case Report. (15th March 2022) - Kobayashi, Yoshikazu; Nakao, Sachie; Okui, Taro; Aizawa, Takako; Satoh, Koji
Study Design: Case Report. Objective: To discuss the case of a 55-year-old man who complained of swelling and pain in the left cheek. Methods: Computed tomographic images showed a shadow of retained electric toothbrush head in the left infratemporal fossa, heterotopic free air, and abscess formation in the masticatory space. Foreign body removal and surgical drainage were performed under general anesthesia. Result: The patient was discharged 6 days postoperatively. Conclusion: Computed tomography should invariably be performed on patients with intraoral impalement injury.